Transforming growth and jobs to reduce poverty. Issue 2 (27th April 2017) - Milasi, Santo; Narasimhan, Veda; Khatiwada, Sameer; Kühn, Stefan
Abstract : The aim of this chapter is, first, to examine the link between economic growth and poverty reduction over time, including an examination of key macroeconomic drivers (section A). Section B analyses in detail the sources of economic growth and the extent to which these may affect its poverty‐reducing impact, underscoring the importance of productive transformation. Finally, section C presents concluding remarks and introduces Part II of the report.